Investigation of layer thickness and cost of flexible pavement designed on subgrade improved with glass powder - Geçkil, Tacettin; Sarıcı, Talha; Karabaş, Bahadır (İdris Karagöz, 2025)
In this study, the effects of improving a clay soil with glass powder (GP) obtained from recycled waste glass on the flexible pavement designed over it were investigated, focusing on layer thickness and construction costs. For this purpose, firstly, some tests were conducted to determine the properties of the soil samples. Subsequently, proctor tests were performed on both soil and specimens prepared by adding 3%, 6%, 9% and 12% GP by weight to the soil. Then, unconfined compression tests were performed on the prepared samples after a curing period of 28 days. The results of the unconfined compression tests showed that the highest strength was obtained from mixtures containing 9% GP. Lastly, following 28 days of curing, California bearing ratio (CBR) tests were conducted on both untreated and 9% GP treated samples, revealing that the CBR value increased by 142.68% with the addition of 9% GP. Based on the obtained CBR values, flexible pavement designs were made on both improved and unimproved soils, and the layer thicknesses and costs were investigated. The calculations indicated that the improvement with 9% GP reduced the pavement layer thicknesses by 31.40% and the costs by 3.44%.

Bu çalışmada, atık camların geri dönüşümünde elde edilen cam tozu (CT) ile kil bir zemini iyileştirmenin, üzerine tasarlanan esnek üst yapıya etkileri, tabaka ve ilk yapım maliyetleri esas alınarak araştırılmıştır. Bu amaçla, ilk olarak zemin örneklerinin özelliklerinin belirlenmesine yönelik bazı deneyler yapılmıştır. Daha sonra zemine ağırlıkça %3, %6, %9, %12 CT ilave edilerek hazırlanmış deney numunelerine proktor deneyi uygulanmıştır. Ardından, hazırlanan serbest basınç deneyi örneklerine 28 gün kür süresi sonrası serbest basınç deneyi yapılmıştır. Serbest basınç deneyleri sonucunda, en yüksek dayanım %9 CT içeren karışımlardan elde edilmiştir. Son olarak, katkısız ve %9 CT katkılı numuneler üzerinde 28 gün kürün akabinde yapılan Kaliforniya taşıma gücü oranı (CBR) deneyleri neticesinde, CBR değerinin %9 CT eklenmesiyle %142,7 arttığı belirlenmiştir. Elde edilen CBR değerleri esas alınarak, iyileştirilen ve iyileştirme yapılmamış zemin üzerine esnek yol üstyapı tasarımı yapılarak üstyapı tabaka kalınlıkları ve maliyetleri araştırılmıştır. Hesaplamalar incelendiğinde, %9 CT ile yapılan iyileştirmenin, üstyapı tabaka kalınlıklarını azalttığı ve maliyetlerini %1,3 oranında düşürdüğü tespit edilmiştir.
Cam tozu kullanılarak iyileştirilen zemininin üzerine tasarlanan esnek üst yapının tabaka kalınlığı ve maliyetinin araştırılması
Keywords: Transportation Engineering; Ulaştırma Mühendisliği